Prokaryotic Cell Wall Compounds Structure and Biochemistry - König, Helmut.; König, Helmut.; Claus, Harald.; Claus, Harald.; Varma, Ajit.; Varma, Ajit. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Microbial cell wall structures play a significant role in maintaining cells’ shape, as protecting layers against harmful agents, in cell adhesion and in positive and negative biological activities with host cells. All prokaryotes, whether they are bacteria or archaea, rely on their surface polymers for these multiple functions. Their surfaces serve as the indispensable primary interfaces between the cell and its surroundings, often mediating or catalyzing important interactions. Prokaryotic Cell Wall Compounds summarizes the current state of knowledge on the prokaryotic cell wall. Topics concerning bacterial and archaeal polymeric cell wall structures, biological activities, growth and inhibition, cell wall interactions and the applications of cell wall components, especially in the field of nanobiotechnology, are presented.